(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the process of introducing digital technologies into the modern education system and its problems related to the quality of education. The use of digital platforms, online learning tools, and information and communication technologies allows for the effective organization of the educational process. At the same time, problems such as insufficient technical infrastructure, low digital competencies of teachers, poor Internet quality, and insufficiently developed independent learning skills of students can affect the quality of education. The article discusses ways to overcome these problems, including improving the digital literacy of teachers, the effective use of modern platforms, and organizing the educational process based on innovative methods.